Arbitral award and enforcement - Ali Mohamed, Ashgar Ali; Kasi, Arun (CLJ Publication, 2020)
Upon hearing the dispute, the arbitrator will make a decision known as an ‘award’. The term ‘award’ means an instrument embodying an arbitrational decision on a matter referred to him. It is the final judgment or decision in writing by an arbitrator or arbitrators and as between the parties and their privies.1 The Arbitration Act 2005 (‘Act’) defines ‘award’ as, ‘a decision of the arbitral tribunal on the substance of the dispute and includes any final, interim or partial award and any award on costs or interest but does not include interlocutory orders’.2 Where an award directs a sum to be paid, that sum shall, unless the award otherwise directs, carry interest as from the date of the award and at the same rate as a judgment debt.3 In any arbitral proceedings with more than one arbitrator, any decision of the arbitral tribunal shall be made by a majority of all its members.4 The award shall be made in writing and shall be signed by the arbitrator. In arbitral proceedings with more than one arbitrator, the signatures of the majority of all members of the arbitral tribunal shall be sufficient, provided that the reason for any omitted signature is stated.